Challenges and Preferences for Online Teaching Practice during Pandemic Time: Student and Teacher Perspectives - Lotulung, Mareike Seska Diana (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
This ongoing study surveyed the challenges of teaching practices in middle and high schools in the Eastern part of Indonesia. The intention was to list the difficulties encountered in online teaching practice and how the teachers and students handle these problems. Data were obtained from an interview transcript and storyline collected from more than 100 students and teachers in more than 100 schools. The focus of the interview ranges from the material, media, instruction and activity, test, and task. The participants also evaluate the effectiveness of these activities compared to the face-to-face classroom practice. Content analysis was used to identify the challenges, with several anecdotes and stories used for triangulation of data and to better illustrate the challenges in school. Another objective of the study was to analyze the preferences over particular teaching practices and particular online teaching platforms. A thematic analysis was used to determine the preference of different types of teaching practices and teaching platforms. This platform included the social media communication used for online classroom communication. The preferences also compared to the remoteness of the area and the background education and professional development of the teachers. On-going conclusion and recommendation were given. Keywords : Online teaching, practices, student perspective, teacher perspective